2008
DOI: 10.1002/zaac.200800359
|View full text |Cite
|
Sign up to set email alerts
|

Tt‐Tt (Tt = Si, Ge) Dumb‐Bell Structures at Different Valence Electron Concentrations: Ln2MgSi2 (Ln = La, Ce), Yb2Li0.5Ge2, and Yb1.75Mg0.75Si2

Abstract: The isostructural compounds Yb 2 MgSi 2 , La 2.05 Mg 0.95 Si 2 , and Ce 2.05 Mg 0.95 Si 2 , as well as Yb 2 Li 0.5 Ge 2 and Yb 1.75 Mg 0.75 Si 2 , respectively, were synthesized from stoichiometric mixtures of the corresponding elements in sealed Nb-ampoules under argon atmosphere. The structures were determined by single crystal X-ray diffraction: Yb 2 MgSi 2 (P4/mbm (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 27 publications
7
24
1
Order By: Relevance
“…A detailed description of our fabrication and characterization of Yb 4 LiGe 4 and Yb 5 Ge 4 samples is presented elsewhere [10], and is generally consistent with the results reported by Xie et al [9]. We present an overview of the process here.…”
Section: Sample Preparation and Characterizationsupporting
confidence: 61%
See 1 more Smart Citation
“…A detailed description of our fabrication and characterization of Yb 4 LiGe 4 and Yb 5 Ge 4 samples is presented elsewhere [10], and is generally consistent with the results reported by Xie et al [9]. We present an overview of the process here.…”
Section: Sample Preparation and Characterizationsupporting
confidence: 61%
“…Detailed studies of the chemistry and structure of this material [9,10] have shown that the Li substitutes for the Yb in lattice sites such that the layers containing Yb 3+ ions are separated by Li containing layers (see Fig. 1),…”
Section: Introductionmentioning
confidence: 99%
“…A partial substitution of triel Ga atoms for tetral Ge ones reduced the VEC and reformed the T1-T1 dimers, resulting in a Sm 5 Ge 4 -to-Gd 5 Si 4 structural transformation. The intimate relationship between the VEC and crystal structure has been also demonstrated in other R 5 T 4 systems through the T substitution, e.g., Gd 5 Si 4Àx Pn x (Pn = P, Sb, Bi) [9][10][11][12], or through the R substitution, such as R 5Àx Ca x Ge 4 (R = La, Ce) [13], R 5Àx Mg x Ge 4 (R = Gd-Lu, Y) [14,15], and Yb 4 LiGe 4 [16].…”
Section: Introductionmentioning
confidence: 79%
“…The slab-center R3 site plays a crucial role in the magnetism of R 5 T 4 and small substitution levels by nonmagnetic atoms for Gd at this site heavily deteriorates the magnetic interaction of Gd 5 Ge 4 [21]. Alkali and alkaline-earth metals were shown to preferentially occupy the R3 site [13][14][15][16] [22,23]. The substitution with smaller/larger atomic size applies positive/negative chemical pressure effect and thus enforces/reduces the magnetic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies are focused on the group-14-element-containing compounds, i.e., silicides [2,3], germanides [4,5] and stannides [6]. Here we reported the crystal structure of a new R5X4 compound without group 14 elements, Y5Ga 1.24 Sb 2.77 .…”
Section: Discussionmentioning
confidence: 97%